Souvenir Khas Dayak dari Hasil Hutan Bukan Kayu Getah Nyatoh: Typical Dayak Souvenirs from Nyatoh Non-wood Forest Products - Nuwa, Nuwa; Rotinsulu, Johanna Maria; Triyadi, Antonius; Prihanika, Prihanika (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Palangka Raya City covers an area of ​​2,687 km2, with a 2015 workforce dominated by high school graduates (27.7%) and university graduates (27.2%). High school graduates were the most unemployed at 2%, followed by vocational high school graduates at 1.4%, and then university graduates at 1% of the total workforce in 2015. This aligns with the Vision and Mission outlined in the RPJMD (Regional Medium-Term Development Plan), namely: